THE IMPORTANCE OF THE CONSTITUTION IN ENHANCING THE LEGAL AWARENESS AND CULTURE OF THE YOUNGER GENERATION - Alimardon Keldiev (Modern American Journals, 2026)
This article examines the key forms of moral and ethical education in shaping the legal consciousness and cultural awareness of youth. It provides a comprehensive analysis of the ways in which moral upbringing contributes to the development of legal literacy, highlighting the critical role of legal education, legal advocacy, and practical engagement with the law. The study emphasizes the interconnectedness of ethical values and legal knowledge in fostering responsible citizenship and social accountability among young people. Furthermore, the article explores how structured moral and legal instruction, coupled with active participation in legal practices, strengthens the ability of youth to understand, interpret, and apply legal norms effectively within the framework of contemporary society.
Keywords: Spirituality, education, law, consciousness, culture, education, science, enlightenment, family, youth, social network, media world.